2021
DOI: 10.3390/cancers13133264
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Correlation between Non-Coding RNA and S-Adenosylmethionine in Human Cancer: Roles and Therapeutic Opportunities

Abstract: Epigenetics includes modifications in DNA methylation, histone and chromatin structure, and expression of non-coding RNAs (ncRNAs), especially microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Knowledge of the relationships between S-adenosylmethionine (AdoMet or SAM), the universal methyl donor for all epigenetic methylation reactions and miRNAs or lncRNAs in human cancer may provide helpful insights for the development of new end more effective anticancer therapeutic approaches. In recent literature, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…It plays a primary role in cellular metabolism and represents the major methyl donor required in numerous methylation reactions [ 55 , 56 , 57 ]. Notably, AdoMet has been found to regulate the expression of miRNAs and lncRNAs through epigenetic mechanisms [ 35 ]. Recently, the effect of AdoMet on miRNA expression profile has been evaluated in breast [ 32 , 33 ] and in head and neck cancer [ 34 ], providing evidence that the ability of AdoMet to inhibit cell proliferation and migration, as well as to induce apoptosis in these tumor cells, is mediated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a primary role in cellular metabolism and represents the major methyl donor required in numerous methylation reactions [ 55 , 56 , 57 ]. Notably, AdoMet has been found to regulate the expression of miRNAs and lncRNAs through epigenetic mechanisms [ 35 ]. Recently, the effect of AdoMet on miRNA expression profile has been evaluated in breast [ 32 , 33 ] and in head and neck cancer [ 34 ], providing evidence that the ability of AdoMet to inhibit cell proliferation and migration, as well as to induce apoptosis in these tumor cells, is mediated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence has also shown that the epigenetic modulation of miRNAs involved in oncogenic functions represents one of the main mechanisms underlying the anticancer activity of AdoMet. The regulation of miRNA’s expression profile by AdoMet has been recently evaluated in breast and in head and neck cancer cells, suggesting that the ability of this natural compound to inhibit proliferation and cell migration, as well as to induce apoptosis in these tumor cells, is mediated by miRNAs [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of AdoMet for cancer prevention has been widely investigated [13,14,22] and much evidence in recent years has highlighted this naturally-occurring multifunctional sulfonium compound as a promising chemosensitizing agent in various cancer types [8][9][10][11][12][13][14]. Interestingly, AdoMet is one of the most widely studied epigenetic regulators and a welldocumented modulator of noncoding RNAs involved in oncogenic functions [35][36][37][38]. The development of combination therapy with natural compounds able to synergize with chemotherapy drugs without causing significant toxic side-effects may represent a promising approach to increase 5-FU sensitivity and prevent drug resistance in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The antimetastatic properties of AdoMet have been well-documented in different types of human cancers, and the underlying mechanisms ranging from epigenetic regulation of genes responsible for cell migration and invasion [33][34][35][36] to the modulation of specific microRNAs (miRNAs) [59,62,63], have been elucidated. In OLSCC, AdoMet inhibits the migration and invasion of Cal-33 and JHU-SCC-011 cells by downregulating the expression of MMP2 and MMP9, two metalloproteinases involved in the degradation of the basement membrane and extracellular matrix.…”
Section: Anticancer Effects Of the Methyl Donor S-adenosylmethionine ...mentioning
confidence: 99%
“…More and more evidence has shown that epigenetic modulation of the level of noncoding RNA involved in oncogenic functions represents one of the mechanisms underlying the anticancer activity of AdoMet. Noncoding RNAs, especially miRNAs, have a significant role in carcinogenesis of head and neck cancers, acting both as oncogenes to promote cancer development and invasion and as tumor suppressors by participating in the modulation of cell proliferation, differentiation, migration, and invasion [63]. Notably, the role of miRNAs as biomarkers in HNSCC has recently been evidenced [67].…”
Section: Anticancer Effects Of the Methyl Donor S-adenosylmethionine ...mentioning
confidence: 99%